Nexus between Organizational Behavior and Managerial Skill of Sports Clubs in Olympic Games - Kuo, Yen-Ku; Shen,Wei-Ting; Kuo, Yen-Lin; Md. Monirul Islam; Edwin Ramirez-Asis; Rumi iqbal doewes, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Volunteers in sports, full-time employees, trainers, coaches, and administrative support personnel all have varying degrees of commitment to their careers and organizations. Athletes are encouraged to participate actively in sports by coaches, parents, and trainers. This benefits players by promoting physical fitness and a healthy lifestyle to increase international and local collaboration. A sports organization comprises a championship, players, managing board, local cooperation, leagues, sports clubs, and men's and women's teams that oversee and conduct the organization's activities. Whether temporary or permanent, sports organizations are tasked with the responsibility of safeguarding the rights of their members. The research design was chosen to collect data using a combination of purposive sampling and snowball sampling. Purposive sampling enabled researchers to select respondents familiar with the requisite degree of knowledge. A questionnaire was used to obtain the data. Fifty respondents took part in this study. Out of 50 responders, 35 were male, and 15 were female. SEM PLS 3.3.7v was used to evaluate the collected data. The findings demonstrated a high positive correlation between the factors.